Construction of Inextensible Flows of Dual Normal Surfaces in the Dual Space D3 - Asil, Vedat; Korpinar, Talat (Soc Paranaense Matematica, 2013)
In this paper, we study dual normal surfaces in dual space D-3. We research inextensible flows of dual normal surfaces of dual curves in dual space D-3.
Keywords: Dual space curve; inextensible flows; Structural mechanics; Dual Frenet frame